Becoming lean: the way towards sustainability of higher educations institutions - Nawanir, Gusman; Binalialhajj, Mohammed; Lim, Kong Teong; Mohd Hanafiah, Ahmad (KnE Social Sciences, 2019)
Sustainability has become a significant issue in today’s business world, including in the education sector. The objective of this cross-sectional study is to examine the implications of lean higher education (LHE) implementation on HEIs sustainability performance. Data were collected from academicians at a technical university in Malaysia. The study found positive relationships between LHE and sustainability performance in terms of environmental, economic, institutional, and social. The finding implies that in order to be sustainable, a university could exert more efforts in implementing LHE practices. This study subsidized to the current literature through bridging the gap of the lacking investigations on the potentials of lean management in the context of HEIs. The Malaysian HEIs could gain benefits through providing alternative solutions and suggestions to improve their business process, moving towards achieving sustainability performance.